2006
DOI: 10.1113/jphysiol.2006.107805
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the histaminergic system during vestibular compensation in the cat

Abstract: To determine how the histaminergic system is implicated in vestibular compensation, we studied the changes in histidine decarboxylase (HDC; the enzyme synthesizing histamine) mRNA regulation in the tuberomammillary (TM) nuclei of cats killed 1 week, 3 weeks and 3 months after unilateral vestibular neurectomy (UVN). We also used one-and two-step bilateral vestibular neurectomized (BVN) cats to determine whether HDC mRNA regulation depended on the asymmetrical vestibular input received by the TM nuclei neurons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 48 publications
(69 reference statements)
4
47
0
2
Order By: Relevance
“…Moreover, in clinical practice, this therapeutic dose of 2 mg/kg is given for several months. In agreement with our findings, Tighilet et al (2006Tighilet et al ( , 2007 reported that this dose had no effect on histidine decarboxylase mRNA expression in control cats after a 1-or 3-week treatment. However, the same low dose acquired an enhancing effect after 3 months (Tighilet et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, in clinical practice, this therapeutic dose of 2 mg/kg is given for several months. In agreement with our findings, Tighilet et al (2006Tighilet et al ( , 2007 reported that this dose had no effect on histidine decarboxylase mRNA expression in control cats after a 1-or 3-week treatment. However, the same low dose acquired an enhancing effect after 3 months (Tighilet et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…In agreement, the systemic administration of thioperamide results in a strong vestibuloplegic effect and strongly depresses the horizontal vestibular-ocular reflex gain (Yabe et al, 1993). It also accelerates the recovery of behavioral functions in the cat after unilateral vestibular neurectomy (Tighilet et al, 2006(Tighilet et al, , 2007.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Nous avons par la suite caractérisé le phénotype de ces nouveaux neurones et trouvé qu'ils exprimaient la GAD67 (glutamic acid decarboxylase 67), enzyme de synthèse du GABA. Les données recueillies en microscopie confocale ont mis en évidence une colocalisation des deux marqueurs BrdU et GAD67 ( Figure 3C) présentes en bordure du IV e ventricule ou encore de certains types d'astrocytes capables de se dédifférencier [26,27]. Une autre piste se dessine également : des progéniteurs pourraient migrer de la zone sous-ventriculaire jusqu'aux NV, en se déplaçant éventuellement le long de vaisseaux sanguins [28,29].…”
Section: Naissance Et Intégration De Nouveaux Neurones Dans Les Noyauunclassified
“…gliales et des astrocytes [24,25], une augmentation de l'efficacité des systèmes GABAergique, cholinergique et histaminergique [20,21,26], ainsi qu'une augmentation du nombre de neurones exprimant le BDNF, le NGF, la neurotrophine 3 (NT3) et leurs récepteurs à activité tyrosine kinase respectifs (TrkA, TrkB et TrkC) [18]. Dans une étude récente, nous avons également observé que les glucocorticoïdes, connus pour entraver la neurogenèse [27], étaient régulés négativement dans les NV après NVU [28].…”
Section: Revuesunclassified